Social network participation towards enactment of self‐care in people with chronic obstructive pulmonary disease: A qualitative meta‐ethnography - Lindsay Welch; Euan Sadler; Anthony Austin; Anne Rogers (Wiley, 2021)
Abstract Background How people with chronic obstructive pulmonary disease (COPD) engage with supportive social networks to enhance self‐care is not understood. The personal rationales for participation in socially directed support have not been addressed in the literature. To determine how people with COPD identify, engage and participate in socially supportive self‐care practices, we conducted a systematic review and meta‐ethnography of qualitative studies. Methods A systematic literature search was conducted between June 2010 and June 2021. Of 3536 articles, 8 fulfilled the inclusion criteria. Using a meta‐ethnography approach to the qualitative synthesis, new concepts were derived from the data to identify aligning themes and develop a conceptual model. Findings Interpretations from the papers yielded concepts of (1) accountability and personal responsibility in self‐care, (2) valued positive relationships with clinicians, (3) understanding of illness through shared and personal experiences and (4) acknowledging social networks in fostering self‐care engagement in people with COPD. The independence‐experience (Index) model of synthesized (third order) interpretations highlighted the processes of social networks and self‐care practices: (a) fear or avoidance of dependency, (b) learning from experiences of adaptive self‐care behaviours and (c) including valued practices in self‐care. Self‐care strategies are formed through illness experiences and relatable social encounters. Conclusion The model derived from the third‐order interpretations is a framework to describe socially supported self‐care and can be used to direct future self‐care strategies and target interventions for people with COPD. Patient or Public Contribution The findings and model were presented to the long‐term conditions patient and public involvement group. The manuscript is coauthored by a public representative.